Tutorial: reading and reviewing the common schema for electrical design and analysis - Parks, C. H. (24th ACM/IEEE Design Automation Conference, 1987)
This tutorial introduces the language, tools, and methods used to develop an information model by an IEEE Task Team. The model identifies the data and data relationships necessary to define electrical products. Reviews are now required for consensus by technical experts who are also familiar with this subject matter. The model will be used to evaluate data transfer formats and establish their mappings without compromising proprietary data structures.